Synthesis of Some Thienyl-Triazine Derivatives and Antimicrobial Activity - Kaplancikli, Z.A.; Turan-Zitouni, G.; Ozdemir, A.; Altintop, M.D.; Tunali, Y. (Asian Journal of Chemistry, 2010)
Some 4-(1-aryl-ethylideneamino)-5-phenyl-1,4-dihydro-2H-[1,2,4]triazine-3-thione derivatives were synthesized and evaluated for their antimicrobial activity. The reaction of 2-acetylfuran or 2-acetyl-thiophene with thiocarbohydrazide yielded the N-(1-arylethylidene) thiocarbohydrazides which furnished the thienyltriazine derivatives by reacting with phenacyl bromides. The chemical structures of the compounds were elucidated by IR, 1H NMR and FAB+-MS spectral data and elemental analyses. Microdilution broth susceptibility assay was used for the antimicrobial activity evaluation of the compounds against the strains Staphylococcus aureus, Enterococcus faecalis, Bacillus subtilis, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia spp., Salmonella thyphimurium, Proteus vulgaris, Listeria monocytogenes, Candida glabrata, Candida albicans, Candida tropicalis. Chloramphenicol and ketoconazole were used as control drugs. A significant level of activity was observed.